2008
DOI: 10.1299/jmsesdm.2008.7.189
|View full text |Cite
|
Sign up to set email alerts
|

DE3-2: A Study on Effect of Heterogeneity of Oxygen Concentration and Temperature Distributions in a Combustion Chamber on Combustion and Emissions of Diesel Engine(DE: Diesel Engine Combustion,General Session Papers)

Abstract: A Study on Effect of Heterogeneity of Oxygen Concentration and Temperature Distributions in a Combustion Chamber on Combustion and Emissions of Diesel Engine " Satoshi TSUDA 7Hidenori KOSAKA, and Tetsuya AIZAWA Department ofMbchanical andAerospace Engineering 7bkyo lhstitute offechnologn 2-12-1 O-okayama, Mbguro-kza fokyo 152-8552 .L4R4N

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Tsuda et al [13] investigated the effect of the heterogeneity of the temperature distribution on the soot and NO x emissions of a diesel flame by using their rapid compression machine, and reported that the NO x and soot emissions from the diesel combustion are governed mainly by the amount of enthalpy entrained into the spray upstream of the ignition region. Their results led the current authors to expect that a simultaneous reduction in the NO x and particulate matter (PM) emissions will be achieved if the heterogeneity of the temperature distribution can be controlled.…”
Section: Possibility Of Controlling the Temperature Stratificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsuda et al [13] investigated the effect of the heterogeneity of the temperature distribution on the soot and NO x emissions of a diesel flame by using their rapid compression machine, and reported that the NO x and soot emissions from the diesel combustion are governed mainly by the amount of enthalpy entrained into the spray upstream of the ignition region. Their results led the current authors to expect that a simultaneous reduction in the NO x and particulate matter (PM) emissions will be achieved if the heterogeneity of the temperature distribution can be controlled.…”
Section: Possibility Of Controlling the Temperature Stratificationmentioning
confidence: 99%
“…As a basic study, Kosaka et al [12,13] investigated the effect of the heterogeneity of oxygen and temperature distribution on the soot and NO x emissions of a diesel flame by using a rapidcompression machine. In their study, mixtures with different oxygen concentrations and temperatures were injected through the intake ports located on the cylinder wall to create a heterogeneous distribution of oxygen and temperature in the combustion chamber.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the authors chose to adopt this term. Even though many researchers have investigated the detailed mechanism that dominates the set-off length, 11,16 it has not yet been fully elucidated. 15,17 Pickett et al 18 proposed an empirical equation based on measurements of a single free-spray flame in a constant-volume vessel L = C Á T À3:74 a Á r À0:85 a Á d 0: 34…”
Section: Introductionmentioning
confidence: 99%
“…13–15 Arai 15 and Fujimoto proposed that the length L be referred to as the “set-off length.” In this study, the authors chose to adopt this term. Even though many researchers have investigated the detailed mechanism that dominates the set-off length, 11,16 it has not yet been fully elucidated. 15,17…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the light duty passenger cars and heavy duty vehicles are still needed and applicable of diesel engines. In addition, the agricultural and industrial sectors are also used diesel engines widely [1][2][3][4][5][6][7]. Therefore, the challenge for the diesel engine today is to reduce raw emission such as Nitrogen Oxide (NO x ), Particular Matter (PM).…”
Section: Introductionmentioning
confidence: 99%